The sequential REE (Rare Earth Elements) extraction of weathered crusts of granitoids from Sibolga, Indonesia. Issue 1 (November 2021) - Setiawan, I
Abstract: Indonesia needs a proven technology for REE extraction to build a national REE industry. Monazite that has been recovered from placer deposits at Bangka-Belitung areas is the most potential REE source. In the future, ion adsorption type will be another potential source of REE deposits. This paper describes the sequential REE extraction of the weathered crusts of granitoids from Sibolga using sequential extraction ICP-MS analysis is applied to determine bulk samples mineralogical compositions and REE content. The total REE (∑REE) content of weathered crusts of granitoids from Sibuluhan Sihaporas A ranges from 265 to 479 ppm, while the amount of ∑REE leached by sequential extraction range from 151 to 263 ppm, and the percentage of adsorbed ∑REE ranges from 55 to 74%. In comparison, Sibuluhan Sihaporas B ranges from 302 to 634 ppm, 82 to 198 ppm, and 28 to 44%, respectively. ∑REE content of weathered granitoids crusts from Sarudik ranges from 135 to 219 ppm, while that SREE leached by sequential extraction range from 21 to 82 ppm, and percentage of adsorbed ∑REE range from 11 to 50 %, while that Sibolga Julu ranges from 191 to 304 ppm, 111 to 138 ppm, and 27 to 44%.